Stromal derived factor‐1α in hippocampus radial glial cells in vitro regulates the migration of neural progenitor cells. (2nd February 2015) - Ding, Hui; Jin, Guo‐Hua; Zou, Lin‐Qing; Zhang, Xiao‐Qing; Li, Hao‐Ming; Tao, Xue‐Lei; Zhang, Xin‐Hua; Qin, Jian‐Bing; Tian, Mei‐Ling
Abstract Stromal derived factor‐1α (SDF‐1α), a critical chemokine that promotes cell homing to target tissues, was presumed to be involved in the traumatic brain injury cortex. In this study, we determined the expression of SDF‐1α in the hippocampus after transection of the fimbria fornix (FF). Realtime PCR and ELISA showed that mRNA transcription and SDF‐1α proteins increased significantly after FF transection. In vitro, the expression of SDF‐1α in radial glial cells (RGCs) incubated with deafferented hippocampus extracts was observed to be greater than in those incubated with normal hippocampus extracts. The co‐culture of neural progenitor cells (NPCs) and RGCs indicated that the extracts of deafferented hippocampus induced more NPCs migrating toward RGCs than the normal extracts. Suppression or overexpression of SDF‐1α in RGCs markedly either decreased or increased, respectively, the migration of NPCs. These results suggest that after FF transection, SDF‐1α in the deafferented hippocampus was upregulated and might play an important role in RGC induction of NPC migration; therefore, SDF‐1α is a target for additional research for determining new therapy for brain injuries.